(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
Starting from the awareness that the immense amount of knowledge produced by the various parliamentary anti-mafia commissions that have succeeded one another over time has remained in many aspects unexplored, the article attempts to systematize the knowledge and the growing awareness acquired by the commissions operating between 1992 and today, trying to highlight their achievements and peaks of efficiency, as well as the major critical issues encountered.